TRANSIENT ELECTROMAGNETIC SOUNDING IN 2D, 3D, AND 4D MODES: SEQUENCE OF GEOLOGICAL EXPLORATION ACTIVITIES - I. V. Buddo; I. A. Shelokhov; N. V. Misyurkeeva; Y. A. Agafonov (Геодинамика и тектонофизика)
From 1980s, electromagnetic prospecting is an integral component of geophysical techniques for oil and gas exploration in many regions of the Russian Federation. Electromagnetic methods are used at all stages of geological exploration, including reconnaissance, discovery, prospecting and appraisal, and economic mining. In oil and gas exploration, the most commonly used technique is the near-field transient electromagnetic sounding (TEM). On the other hand, for each of these stages, specific tasks of electromagnetic prospecting have not been clearly defined yet. Furthermore, there are no standard requirements to the volume of a priori geological and geophysical information, which is sufficient for solving a geological problem. If such information is lacking or insufficient, a geological problem may be incorrectly stated and/or improperly correlated with the current stage of works. Our study aims to define which geological problems should be addressed by electromagnetic survey at the different stages of geological exploration, and to specify the requirements to the availability of a priori geological and geophysical information. We have analyzed the electromagnetic data from the regions of East and West Siberia, which have different geological settings. The main geological problems that can be solved by the seismic and electromagnetic techniques are determined. We propose a set of geophysical survey operations, which is optimal for oil and gas exploration. An effective sequence of electromagnetic prospecting stages is determined, and preliminary and accompanying surveys are specified. The requirements to the availability of a priori information are proposed, and its volume is defined. Geological problems are defined with respect to the corresponding stages of geological exploration. Special attention is given to approaches to the mineral resource estimation and calculation of hydrocarbon reserves, taking into account electromagnetic survey results. It is proposed to use the electromagnetic data at the stage of prospecting and appraisal, which aims to assess the resources of categories Dl and D0, as well as at the exploration stage for estimating the reserves of category C2 in new and explored fields. Approaches to the economic assessment of using electromagnetic surveys as part of the geological exploration are discussed. Our study shows that a correct sequence of electromagnetic prospecting operations at each stage can ensure obtaining an original geological dataset of the given stage and thus providing a proper basis for the next stage of oil-gas field investigation.